2009
DOI: 10.4049/jimmunol.0900238
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Underlying Distinct T Cell-Dependent Polysaccharide-Specific IgG Responses to an Intact Gram-Positive Bacterium versus a Soluble Conjugate Vaccine

Abstract: IgG anti-polysaccharide (PS) responses to both intact Streptococcus pneumoniae (Pn) and PS conjugate vaccines are dependent on CD4+ T cells, B7-dependent costimulation, and CD40-CD40-ligand interactions. Nevertheless, the former response, in contrast to the latter, is mediated by an ICOS-independent, apoptosis-prone, extrafollicular pathway that fails to generate PS-specific memory. We show that pre-existing PS-specific Igs, the bacterial surface or particulation, selective recruitment of B cell subsets, or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 33 publications
3
65
0
Order By: Relevance
“…This is consistent with the augmented MCPS-specific IgG response observed in MenC-primed mice following booster immunization with isolated MCPS, also a TI Ag, or a soluble covalent conjugate of MCPS and TT. Results similar to that obtained with MenC are also observed using another GN bacteria, A. baumannii expressing PNAG, that is, a primary PNAG-specific IgG response that peaks relatively late (by day [14][15][16][17][18][19][20][21] and that is independent of CD4 + T cells, and an augmented PNAG-specific IgG response following booster immunization with A. baumannii that requires CD4 + T cells during the primary, but not during the booster immunization. These data further support the notion that the regulation of capsular PSspecific IgG responses to intact bacteria is dependent on the nature of the subcapsular domain, and suggest a potential, general dichotomy between GP and GN bacteria.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is consistent with the augmented MCPS-specific IgG response observed in MenC-primed mice following booster immunization with isolated MCPS, also a TI Ag, or a soluble covalent conjugate of MCPS and TT. Results similar to that obtained with MenC are also observed using another GN bacteria, A. baumannii expressing PNAG, that is, a primary PNAG-specific IgG response that peaks relatively late (by day [14][15][16][17][18][19][20][21] and that is independent of CD4 + T cells, and an augmented PNAG-specific IgG response following booster immunization with A. baumannii that requires CD4 + T cells during the primary, but not during the booster immunization. These data further support the notion that the regulation of capsular PSspecific IgG responses to intact bacteria is dependent on the nature of the subcapsular domain, and suggest a potential, general dichotomy between GP and GN bacteria.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies using intact heat-killed S. pneumoniae and a soluble pneumococcal conjugate vaccine strongly suggested that PS-specific IgG responses were derived from marginal zone and follicular B cells, respectively (18,19), with elicitation of distinct idiotypes on the PS-specific (serotype 14) IgG (17). Indeed, mice primed with intact serotype 14 S. pneumoniae do not elicit an augmented PS-specific IgG response following booster immunization with a soluble type 14 pneumococcal conjugate vaccine, in which the carrier protein is pneumococcal surface protein A (33), but do elicit an augmented response following booster immunization with intact GBS-III expressing type 14 PS (21).…”
Section: Mice Primed With Either Menc or A Soluble Conjugate Of Mcps-mentioning
confidence: 99%
See 1 more Smart Citation
“…This dichotomy was specifically dependent on whether the PS was coexpressed with protein in a particulate or soluble form (24). Of note, although alum adjuvant is particulate, Ag adsorbed to alum did not behave as a particulate Ag (22). In this regard, DCs exposed to alum-adsorbed Ag exhibited facilitated Ag uptake but did not internalize the alum particles (25).…”
Section: Endritic Cells (Dc) Monocytes (And Monocyte-derived Cellsmentioning
confidence: 84%
“…We demonstrated previously that polysaccharide (PS)-and protein-specific IgG responses to intact extracellular bacteria (20), as well as soluble conjugate vaccines (21), are dependent on CD4 + T cells. However, the PS-specific IgG response to an intact bacterium arose from MZ B cells expressing a distinct and dominant idiotype, in contrast to the same PS-specific IgG response to a soluble conjugate vaccine, which arose from follicular B cells expressing a different idiotype(s) (21)(22)(23). This dichotomy was specifically dependent on whether the PS was coexpressed with protein in a particulate or soluble form (24).…”
Section: Endritic Cells (Dc) Monocytes (And Monocyte-derived Cellsmentioning
confidence: 91%